A contemporary theory of social entrepreneurship for sustainable wealth creation - Mhd. Sarif, Suhaimi (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
This book contains nine chapters. In Chapter One, Suhaimi Mhd Sarif and Yusof Ismail provide an introduction to the topic of contemporary theory of social entrepreneurship. As for Chapter Two, Mohd Ali Bahari and Suhaimi Mhd Sarif proposed that the historical development of social entrepreneurship is not entirely different from the development of entrepreneurship in the study of the firm. In Chapter Three, Mohd Ali Bahari and Suhaimi Mhd Sarif portrayed the social entrepreneurship development in Malaysia.